Profile of Students' Physics Critical Thinking Skills and Application of Problem Based Learning Models Assisted by Digital Books in Physics Learning in High School - Shalsa Billa Ardhana Neswary; Binar Kurnia Prahani (Postgraduate, University of Mataram, 2022)
This research aims to analyze the profile of students' critical thinking skills and the application of Problem Based Learning (PBL) models based on digital books on physics learning in high school. This research method is a preliminary study with data collection techniques in the form of written tests whose data results will be analyzed descriptively qualitatively. The study was conducted on 176 students consisting of 77 male students and 99 female students. in 5 classes X MIPA at one of the State High Schools in Sidoarjo Regency. It was concluded that: 1) The lowest criteria for critical thinking skills of students were found in the analysis indicator with an average score of 0.989 in female students and 0.636 in male students. 2) Students' critical thinking skills belong to the low category, the score range of 0-45 as many as 99 female students and 77 male students and no students who belong to the medium and high categories. In this study, the application of digital book-assisted PBL is expected to improve students' critical thinking skills. So, it was concluded that if the critical thinking skills that students have are low, then it is necessary to improve students' critical thinking skills, namely with the implementation of digital book-assisted PBL models